2013
DOI: 10.1177/2150131913495739
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Diagnosis and Management of Childhood Obesity/Overweight in Primary Care

Abstract: Objective: To determine the temporal trends in diagnosis and management of pediatric overweight/obesity by primary care providers at a single medical center. Patients: Children 2 to 18 years old undergoing a general medical examination during 3 calendar years (2003, 2006, and 2009) Conclusions: There has been steady improvement in the rates of obesity diagnosis and obesity-related counseling by primary care providers. However, continued efforts to increase awareness of these issues are needed as nearly half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Missing data were notable in uninsured patients and in those living rurally or in areas of high economic hardship. BMI data are becoming more readily available within the EHR, 3642 making it increasingly feasible for EHR data to become an agile and cost-effective 5 public health tool for local childhood obesity prevention efforts. 8 EHR data are collected directly from the community during clinic visits and, unlike other data sets, do not rely upon imputed estimates from non-indigenous samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missing data were notable in uninsured patients and in those living rurally or in areas of high economic hardship. BMI data are becoming more readily available within the EHR, 3642 making it increasingly feasible for EHR data to become an agile and cost-effective 5 public health tool for local childhood obesity prevention efforts. 8 EHR data are collected directly from the community during clinic visits and, unlike other data sets, do not rely upon imputed estimates from non-indigenous samples.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of BMI data is anticipated to improve with universal insurance coverage and as health systems implement successful quality assurance and outreach efforts. 3642 …”
Section: Discussionmentioning
confidence: 99%
“…Many PCPs cite lack of time as a barrier to weight management counseling, even in regards to making a referral. 4,5,30 PCPs are seeing multiple patients in one day and typically they come for another purpose unrelated to weight. While patient volume for PCPs will not decrease, if they lack time for counseling on weight management that is more of a reason to refer those patients to a weight management program.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that most PCPs reported as lacking in primary care was increased time for counseling (85%). Many PCPs cite lack of time as a barrier to weight management counseling, even in regards to making a referral [4,5,30]. PCPs are seeing multiple patients in one day and typically they come for another purpose unrelated to weight.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported lack of time as a constraint in providing weight management counseling, specifically limited time for each patient visit [4,5]. Many providers feel they do not have time for appropriate counseling related to obesity [30,31]. According to Rice et al [6], lack of time and reimbursement of time for weight management counseling was a barrier to referring patients.…”
Section: Literature Reviewmentioning
confidence: 99%